Higher-order thought and the problem of shifting subjectivity - Chaturvedi, Madhu Mangal (Array, 2019)
In this paper, we argue that the two versions of the higher–order thought theory of consciousness, viz. Rosenthal’s extrinsic higher–order thought and Gennaro’s intrinsic higher–order thought, fail to explain the subjective character of a conscious mental state. Both these theories face what we call the problem of shifting subjectivity. Since these theories explain the consciousness of mental states in terms of a representational relation between two unconscious mental states with the help of a two–tiered representational structure divided into a higher–order thought and a lower–order mental state (which is the target of the higher–order thought), they fail to explain the subjective character of conscious mental states, which is intrinsic to them. In their account, the subjective character intrinsic to conscious mental states seems to shift from the target state to the higher–order mental state, which is separate from the target state. The objection is strong against Rosenthal’s extrinsic higher–order thought theory, which clearly makes a distinction between a world–directed mental state and the higher–order thought representing it. However, although Gennaro’s intrinsic higher–order thought theory is an attempt to preserve the intuition that consciousness is intrinsic to conscious mental states, it faces the problem of shifting subjectivity in the case of introspective consciousness.